Questões linguísticas no ensino fundamental ii na Guiné-Bissau: entrevistas com agentes educacionais - Balde, Maimuna (Universidade Federal de São Carlos, 2025)
This work aims to understand the perceptions of educational agents regarding linguistic issues in primary education in Guinea-Bissau. Given that the country is considered multilingual, children are taught in Portuguese in school environments, although for most of them, this is not their first language. The methodology of this work is qualitative and quantitative, through a bibliographic and ethnographic approach based on the theories of Cabral (1976), Almeida Filho (2005), Couto and Embaló (2010). In addition, we conducted interviews with teachers and principals from two schools. The hypothesis of this work contextualizes the challenges in the process of learning the Portuguese language in primary education in Guinea-Bissau, which negatively impact the learning of content by Guinean students. We started from the assumption that it would be necessary to readapt the method applied in elementary school II (basic education) in relation to the Portuguese language, in order to establish mechanisms that bring students closer to the content, starting with the inclusion of Guinean alongside Portuguese. Regarding the analysis of research data generated with the teaching staff, it is pointed out that the Portuguese language generates enormous challenges for students, including some teachers, since a significant portion of the teachers themselves claim to have greater command of Guinean, even those with a degree in Letters/Portuguese Language. However, despite showing greater linguistic fluency in Guinean, they argue that it is necessary to learn the Portuguese language because it is the official language of the State, justifying that, based on this premise of official status, all citizens have the right to learn it. We understand that, to minimize the linguistic challenges for teachers and students, and also to advance the learning process of languages of various statuses, each with its role in the lives of citizens, it is important to balance both in teaching (Portuguese and Guinean). Therefore, we conclude that there is a huge need for the government to implement bilingual education, considering the linguistic context of the country
Linguistic issues in middle school education in Guinea-Bissau: interviews with educational agents
Keywords: Ensino bilíngue; Ensino fundamental guineense; Desafios linguísticos; Bilingual education; Guinean primary education; Linguistic challenges; CIENCIAS HUMANAS::EDUCACAO; 4. Educação de Qualidade